Epoxy resin composition and application thereof

By combining modified boron nitride and epoxy resin, the problem of thermal conductivity fillers in the prior art cannot be filled in large quantities and the bonding performance is reduced, and a metal foil laminate with high thermal conductivity, peel strength and bonding performance is achieved.

CN119708761AActive Publication Date: 2025-03-28SHAANXI SHENGYI TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411949264.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The thermal conductivity fillers such as boron nitride in existing copper clad materials cannot be filled in large quantities due to the sheet layered structure, resulting in limited improvement in thermal conductivity. At the same time, the increase in thermal conductivity will reduce the bonding performance and affect the reliability of copper clad sheet.

Method used

Modified boron nitride particles are prepared by sintering and crushing a specific type and amount of sintering aid and combined with epoxy resin to design a high-filling ratio epoxy resin composition.

Benefits of technology

The epoxy resin composition has high peel strength and excellent bonding properties while having high thermal conductivity, thereby improving the comprehensive performance of the metal-covered foil laminate, including high thermal conductivity and high reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides an epoxy resin composition and application thereof. The epoxy resin composition comprises a combination of epoxy resin, a curing system and modified boron nitride, the modified boron nitride is prepared by adopting the following method, and the method comprises the following steps: mixing boron nitride and a sintering aid, sintering and crushing to obtain the modified boron nitride. According to the invention, boron nitride and a specific type and dosage of sintering aid are sintered and then crushed, and through the design of a modification method, the modified boron nitride has a high filling ratio in epoxy resin, and the epoxy resin composition containing the modified boron nitride has high peel strength and excellent adhesive property while realizing high thermal conductivity, so that the service life of the epoxy resin composition is prolonged. Therefore, the metal foil-coated laminated board has excellent comprehensive effects in the aspects of high heat conductivity and high reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper clad laminates, and particularly relates to an epoxy resin composition and application thereof. Background Art

[0002] As electronic products develop towards high density, multi-function, and "light, thin, and small", the power consumption of devices is increasing, the assembly density and integration of components on circuit boards are getting higher and higher, and the heat dissipated per unit area of ​​circuit boards during operation is increasing. If the heat dissipation of the substrate is not good, the temperature of the components on the circuit board will be too high, which will reduce the working stability and reliability of the whole machine, and even cause product failure and shorten the service life of the product. In order to ensure the working stability of electronic components, higher requirements are placed on the heat dissipation of the board.

[0003] In order to improve the thermal conductivity of the substrate, high thermal conductivity materials are usually introduced into the preparation of the dielectric layer and the copper clad laminate, such as resins with good thermal conductivity, thermal conductive fillers, etc.; since the types of resins with good thermal conductivity are relatively limited and the cost is high, adding thermal conductive fillers is the main method. For example, CN102993996A discloses a high thermal conductive adhesive film for copper clad laminates, and its preparation raw materials include: 25-35 parts of epoxy resin, 65-75 parts of thermal conductive fillers, 30-40 parts of solvents, and 10-20 parts of curing agents. CN116080213A discloses a high thermal conductivity and high heat resistance CEM-3 copper clad laminate, wherein the raw materials for preparing the core material include: 10-50% long-chain polymer epoxy resin, 10-40% solid phenolic resin, 40-60% brominated epoxy resin, 0.10-0.80% imidazole catalyst, 10-30% inorganic filler, 10-60% flame retardant filler, and 40-70% high thermal conductivity powder; the surface material preparation includes the following raw materials in weight percentage: 10-40% phosphorus-containing epoxy resin, 40-60% brominated epoxy resin, 0.10-0.80% imidazole catalyst, 0.1-1% dicyandiamide, and 10-60% flame retardant filler; wherein the inorganic filler is one or a mixture of spherical silicon micropowder and titanium dioxide, and the main component of the high thermal conductivity powder is nitrogen aluminum oxide. CN103694644A discloses an epoxy resin composition, which comprises the following components by mass: 90-110 parts of epoxy resin, 10-50 parts of thermoplastic resin, 1-100 parts of curing agent, 0.05-5 parts of curing accelerator, 1-10 parts of additives, and 20-500 parts of thermal conductive fillers; wherein the thermal conductive filler is one or more of zinc oxide, magnesium oxide, aluminum oxide, bismuth oxide, beryllium oxide, magnesium hydroxide, aluminum hydroxide, silicon dioxide, iron oxide, boron nitride, silicon nitride, silicon carbide, diamond, and silicon nitride; the epoxy resin composition can improve the thermal conductivity and insulation of composite materials and copper clad laminates.

[0004] At present, the thermal conductive fillers used in copper clad laminate materials mainly include aluminum oxide, aluminum nitride, boron nitride, boron oxide, silicon carbide, etc. Among them, boron nitride, as a filler material with excellent thermal conductivity, has great potential in thermal conductive materials. However, boron nitride has a lamellar structure and a large specific surface area, so it cannot be filled in large quantities in the resin, which greatly weakens the ability of boron nitride to improve the thermal conductivity of composite materials. Moreover, the increase in the amount of thermal conductive filler will also lead to the deterioration of the bonding performance between the adhesive layer and the copper foil and the metal substrate, thereby weakening a series of properties of the copper clad laminate such as heat resistance and voltage resistance, resulting in poor reliability of the substrate.

[0005] Therefore, developing a composite material with high thermal conductivity and excellent bonding properties is an urgent problem to be solved in the art. Summary of the invention

[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an epoxy resin composition and its application. By designing a preparation method, a modified boron nitride with high thermal conductivity and a high filling ratio is obtained, so that the epoxy resin composition containing the modified boron nitride has high thermal conductivity, high peel strength and excellent bonding performance, thereby enabling the metal foil-clad laminate to achieve excellent comprehensive performance in terms of high thermal conductivity and high reliability.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides an epoxy resin composition, comprising a combination of an epoxy resin, a curing system and modified boron nitride.

[0009] The modified boron nitride is prepared by the following method, which includes: mixing boron nitride and a sintering aid, and sintering and crushing to obtain the modified boron nitride.

[0010] The sintering aid includes any one of calcium oxide, magnesium oxide, silicon oxide, yttrium oxide, niobium oxide, and potassium feldspar, or a combination of at least two thereof; based on the total mass of the boron nitride and the sintering aid being 100%, the mass of the sintering aid is 1-10%.

[0011] The present invention subjects boron nitride and a specific type of sintering aid to high-temperature sintering and crushing to obtain the modified boron nitride particles. Under the synergistic effect of the sintering aid and sintering, the filling ratio of the modified boron nitride particles in the epoxy resin can be significantly improved, so that the epoxy resin composition can achieve higher thermal conductivity while also having high peel strength and excellent bonding performance, thereby significantly improving the comprehensive performance of the metal foil-clad laminate in terms of heat dissipation and reliability.

[0012] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0013] Preferably, the boron nitride includes hexagonal boron nitride and / or cubic boron nitride, and hexagonal boron nitride is further preferred.

[0014] In the present invention, taking the total mass of the boron nitride and the sintering aid as 100%, the mass of the sintering aid is 1-10%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8% or 9%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0015] The present invention mixes a specific type and amount of sintering aid with boron nitride, and then sintering and crushing to obtain a specific modified boron nitride, which overcomes the defect that lamellar boron nitride cannot be filled in large quantities, resulting in insufficient thermal conductivity of the material. The modified boron nitride has excellent thermal conductivity and a high filling ratio in epoxy resin, so that the epoxy resin composition containing it has both high thermal conductivity and high peel strength. If the amount of the sintering aid is less than 1%, it is difficult to effectively modify the boron nitride and the filling ratio of boron nitride in the resin cannot be increased; if the amount of the sintering aid is greater than 10%, the thermal conductivity of the modified boron nitride and the epoxy resin composition containing it will be reduced.

[0016] Preferably, the epoxy resin includes any one or a combination of at least two of bisphenol A epoxy resin, bisphenol F epoxy resin, phenolic epoxy resin, phosphorus-containing epoxy resin, isocyanate-modified epoxy resin, novolac epoxy resin, biphenyl epoxy resin, dicyclopentadiene epoxy resin, naphthalene-containing epoxy resin, alicyclic epoxy resin, and brominated epoxy resin.

[0017] Preferably, the isocyanate-modified epoxy resin includes MDI (diphenylmethane diisocyanate)-modified epoxy resin.

[0018] Preferably, the mass percentage of epoxy resin in the epoxy resin composition is 8-70%, for example, it can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or 65%, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively enumerates the specific points included in the range, and 9-50% is further preferred.

[0019] Preferably, the mass percentage of the curing system in the epoxy resin composition is 0.01-30%, for example, it can be 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 25% or 28%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0020] Preferably, the curing system comprises a curing agent and / or an accelerator.

[0021] Preferably, the curing agent includes any one of phenolic resin, cyanate resin, active ester, modified polyphenylene ether resin, maleimide resin, anhydride curing agent, amine curing agent, and benzoxazine resin, or a combination of at least two thereof.

[0022] Preferably, the phenolic resin includes any one or a combination of at least two of bisphenol A type phenolic resin, phosphorus-containing phenolic resin, phenol-type phenolic resin, biphenyl-type phenolic resin, dicyclopentadiene-type phenolic resin, and naphthalene-containing phenolic resin.

[0023] Preferably, the modified polyphenylene ether resin includes any one of hydroxyl-terminated polyphenylene ether resin, amino-terminated polyphenylene ether resin, and anhydride-terminated polyphenylene ether resin, or a combination of at least two of them.

[0024] Preferably, the mass percentage of the curing agent in the epoxy resin composition is ≤20%, for example, it can be 0, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16% or 18%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0025] Preferably, the accelerator includes any one of imidazole compounds, organic complexes, tertiary amines, tertiary phosphines, and quaternary ammonium salts, or a combination of at least two thereof, and imidazole compounds are further preferred.

[0026] It should be noted that the imidazole compound, as an accelerator, can simultaneously play the role of curing the epoxy resin and accelerating the curing.

[0027] Preferably, the imidazole compound includes any one of 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole, 1-benzyl-2-methylimidazole, 2-heptadecylimidazole, 2-isopropylimidazole, 2-phenyl-4-methylimidazole, 2-dodecylimidazole, and 1-cyanoethyl-2-methylimidazole, or a combination of at least two thereof.

[0028] Preferably, the mass percentage of the accelerator in the epoxy resin composition is ≤8%, for example, it can be 0, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7% or 7.5%, and specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively enumerates the specific points included in the range, and 0.01-6% is further preferred.

[0029] Preferably, the average particle size of the modified boron nitride is 0.1-30 μm, for example, it can be 0.2 μm, 0.5 μm, 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm or 28 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0030] In the present invention, the average particle size can be understood as D 50 Particle size, relevant data of particle size can be obtained by testing using MS3000 Malvern laser particle size analyzer.

[0031] In the present invention, the mass percentage of modified boron nitride in the epoxy resin composition can be adjusted according to the requirements of thermal conductivity, processability of the board, peel strength, reliability and other properties, and can be 10-92%, more preferably 20-92%.

[0032] Preferably, the mass percentage of modified boron nitride in the epoxy resin composition is 30-92%, for example, it can be 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, and specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 50-90% is further preferred.

[0033] As a preferred technical solution of the present invention, the mass percentage of modified boron nitride in the epoxy resin composition is 30-92%, and more preferably 50-90%, thereby making the epoxy resin composition and the metal foil-clad laminate prepared therefrom have high thermal conductivity, high peel strength and excellent reliability. If the content of modified boron nitride is too low, the thermal conductivity of the material will be reduced; if the content of modified boron nitride is too high, the processability of the epoxy resin composition will be deteriorated, and it will be difficult to produce a qualified plate.

[0034] Preferably, in the method for preparing modified boron nitride, the mixed raw materials also include other metal oxides.

[0035] In the present invention, the "other metal oxide" refers to a metal oxide other than the sintering aid.

[0036] Preferably, the other metal oxides include aluminum oxide and / or beryllium oxide.

[0037] Preferably, based on the total mass of the boron nitride, sintering aids and other metal oxides as 100%, the mass of the other metal oxides is ≤10%, for example, it can be 0, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8% or 9%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 1-10% is more preferred.

[0038] Preferably, the mixing method comprises physical dry mixing.

[0039] Preferably, the mixing time is 0.1-3h, for example, it can be 0.2h, 0.4h, 0.5h, 0.8h, 1h, 1.2h, 1.5h, 1.8h, 2h, 2.2h, 2.5h or 2.8h, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0040] Preferably, the sintering is performed in an inert atmosphere.

[0041] Preferably, the inert atmosphere includes a nitrogen atmosphere and / or an argon atmosphere.

[0042] Preferably, the sintering method includes a one-stage sintering method or a two-stage sintering method.

[0043] It should be noted that, no matter the one-stage sintering method or the two-stage sintering method, the sintering process is carried out in an inert atmosphere (preferably a nitrogen atmosphere and / or an argon atmosphere).

[0044] Preferably, the sintering temperature of the one-stage sintering method is 700-2000°C, for example, it can be 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C or 1900°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0045] Preferably, the sintering pressure of the one-stage sintering method is 1-10 GPa, for example, it can be 2 GPa, 3 GPa, 4 GPa, 5 GPa, 6 GPa, 7 GPa, 8 GPa or 9 GPa, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0046] Preferably, the sintering time of the one-stage sintering method is 2-8 h, for example, it can be 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h or 7.5 h, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0047] As a preferred technical solution of the present invention, as a one-stage sintering method, by carrying out the sintering in an inert atmosphere and controlling the sintering temperature to 700-2000°C, the pressure to 1-10GPa, and the time to 2-8h, the modified boron nitride can have high thermal conductivity while further improving its filling ratio in the epoxy resin.

[0048] Preferably, the two-stage sintering method comprises: mixing boron nitride, a sintering aid and optionally other metal oxides, performing a first sintering and a first crushing to obtain primary particles; and performing a second sintering and a second crushing on the primary particles to obtain the modified boron nitride.

[0049] Preferably, the first sintering temperature is 300-700°C, for example, it can be 350°C, 400°C, 450°C, 500°C, 550°C, 600°C or 650°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0050] Preferably, the first sintering pressure is 1-10 GPa, for example, it can be 2 GPa, 3 GPa, 4 GPa, 5 GPa, 6 GPa, 7 GPa, 8 GPa or 9 GPa, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0051] Preferably, the first sintering time is 1-8h, for example, it can be 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h or 7.5h, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0052] Preferably, the average particle size of the primary particles is 0.1-50 μm, for example, it can be 0.2 μm, 0.5 μm, 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, 35 μm, 40 μm or 45 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0053] Preferably, the temperature of the second sintering is 700-2000°C, for example, it can be 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C or 1900°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0054] Preferably, the second sintering time is 2-8h, for example, it can be 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h or 7.5h, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0055] As another preferred technical solution of the present invention, a mixture containing boron nitride, a sintering aid and optionally other metal oxides is sintered in two stages, wherein the first sintering is carried out at high temperature and high pressure, the temperature is 300-700°C, the pressure is 1-10GPa, and the time is 1-8h; the second sintering is carried out at high temperature, the temperature is 700-2000°C, the time is 2-8h, and no additional pressure is required for the second sintering. By designing and optimizing the two sintering processes, the filling ratio of the modified boron nitride in the epoxy resin can be further improved.

[0056] Preferably, the crushing method (first crushing, second crushing) includes ball milling, for example, wet ball milling.

[0057] Preferably, the rotation speed of the ball mill is 500-5000rpm, for example, it can be 1000rpm, 1500rpm, 2000rpm, 2500rpm, 3000rpm, 3500rpm, 4000rpm or 4500rpm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0058] Preferably, the ball milling time is 0.5-6h, for example, it can be 0.8h, 1h, 1.2h, 1.5h, 1.8h, 2h, 2.2h, 2.5h, 2.8h, 3h, 3.2h, 3.5h, 3.8h, 4h, 4.2h, 4.5h, 4.8h, 5h or 5.5h, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0059] Preferably, the epoxy resin composition further comprises any one of a filler, a flame retardant, and a coupling agent, or a combination of at least two of them.

[0060] Preferably, the filler includes any one of silicon dioxide, titanium dioxide, barium titanate, strontium titanate, magnesium titanate, calcium titanate, barium strontium titanate, calcium barium titanate, lead titanate, lead zirconate titanate, lead lanthanum zirconate titanate, barium lanthanum titanate, barium zirconate titanate, hafnium dioxide, lead magnesium niobate, barium magnesium niobate, lithium niobate, potassium niobate, strontium aluminum tantalate, potassium tantalum niobate, barium strontium niobate, lead barium niobate, barium titanium niobate, strontium bismuth tantalate, bismuth titanate, barium rubidium titanate, copper titanate, and lead titanate-lead magnesium niobate, or a combination of at least two of them.

[0061] Preferably, the average particle size (D 50 The particle size) is 0.01-50 μm, for example, it can be 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, and specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively enumerates the specific point values ​​included in the range. It is further preferred to be 0.01-30 μm, and even more preferred to be 0.01-10 μm.

[0062] Preferably, the mass percentage of filler in the epoxy resin composition is ≤20%, for example, it can be 0, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16% or 18%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0063] A solvent may also be added to the above epoxy resin composition, and the amount of solvent added is selected by a person skilled in the art based on experience and process requirements, so that the epoxy resin composition reaches a viscosity suitable for use, so as to facilitate impregnation, coating, etc. of the epoxy resin composition. In the subsequent drying, semi-curing or full curing stage, the solvent in the epoxy resin composition will partially or completely volatilize.

[0064] In another aspect, the present invention provides a resin adhesive, wherein the resin adhesive comprises the epoxy resin composition as described in the first aspect and a solvent.

[0065] Illustratively, the solvent includes any one of a ketone solvent, an alcohol solvent, an aromatic hydrocarbon solvent, an ester solvent, and a nitrogen-containing solvent, or a combination of at least two thereof.

[0066] The solvent of the present invention is not particularly limited, and generally, ketones such as acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, aromatic hydrocarbons such as toluene, xylene, and mesitylene, esters such as ethyl acetate, butyl acetate, and ethoxyethyl acetate, alcohols such as methanol, ethanol, and butanol, ethers such as ethyl cellosolve, butyl cellosolve, ethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, carbitol, and butyl carbitol, and nitrogen-containing solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone can be used; the solvent can be used alone or in combination of two or more.

[0067] The epoxy resin composition provided by the present invention is prepared by the following method, which comprises: mixing and uniformly dispersing the components in the epoxy resin composition to obtain the epoxy resin composition.

[0068] In a second aspect, the present invention provides a prepreg, comprising a reinforcing material and the epoxy resin composition as described in the first aspect attached to the reinforcing material.

[0069] Preferably, the epoxy resin composition is attached to the reinforcing material by impregnation and drying.

[0070] Illustratively, the method for preparing the prepreg is: using the resin glue of the epoxy resin composition to impregnate a reinforcing material, and then drying to obtain the prepreg.

[0071] Preferably, the drying temperature is 100-180°C, for example, it can be 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C or 175°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 115-175°C is further preferred.

[0072] Preferably, the drying time is 1-30 min, for example, it can be 2 min, 5 min, 8 min, 10 min, 15 min, 20 min or 25 min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 2-15 min is further preferred.

[0073] In a third aspect, the present invention provides a thermally conductive resin film, wherein the material of the thermally conductive resin film includes the epoxy resin composition as described in the first aspect.

[0074] Preferably, the thermally conductive resin film is obtained by coating the epoxy resin composition on a release material and then drying and / or semi-curing the epoxy resin composition.

[0075] In another aspect, the present invention provides a resin-coated copper foil, wherein the resin-coated copper foil comprises a copper foil layer and a resin layer, wherein the material of the resin layer comprises the epoxy resin composition as described in the first aspect.

[0076] Preferably, the resin-coated copper foil is obtained by coating the epoxy resin composition on a copper foil and then drying and / or semi-curing the composition.

[0077] In a fourth aspect, the present invention provides a metal foil-clad laminate, comprising a metal foil and at least one of the prepreg described in the second aspect and the thermally conductive resin film described in the third aspect.

[0078] Preferably, the metal foil in the metal foil-clad laminate includes any one of copper foil, aluminum foil, nickel foil, alloy foil, or a combination of at least two of them.

[0079] Preferably, the metal foil is copper foil, and the metal foil-clad laminate is a copper-clad laminate.

[0080] Preferably, the number of prepregs in the metal foil-clad laminate is 1-20, for example, 2, 3, 5, 7, 9, 10, 11, 13, 15, 17 or 19, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0081] Exemplarily, the method for preparing the metal foil-clad laminate comprises: laminating metal foil on one side or both sides of a prepreg and curing to obtain the metal foil-clad laminate; or, stacking at least two prepregs into a laminate, and then laminating metal foil on one side or both sides of the laminate and curing to obtain the metal foil-clad laminate.

[0082] Preferably, the curing is carried out in a press.

[0083] Preferably, the curing temperature is 170-280°C, for example 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C or 270°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0084] Preferably, the curing pressure is 1-10 MPa, for example 1.5 MPa, 2 MPa, 3 MPa, 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa or 9 MPa, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0085] Preferably, the curing time is 30-300 min, for example 40 min, 50 min, 60 min, 80 min, 100 min, 120 min, 150 min, 180 min, 200 min, 220 min, 240 min, 260 min or 280 min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0086] In another aspect, the present invention provides a printed circuit board, comprising at least one of the prepreg described in the second aspect, the thermally conductive resin film described in the third aspect, and the metal foil-clad laminate described in the fourth aspect.

[0087] Compared with the prior art, the present invention has the following beneficial effects:

[0088] (1) In the epoxy resin composition provided by the present invention, boron nitride is sintered with a sintering aid of a specific type and amount and then crushed. By designing a modification method, the modified boron nitride has a high filling ratio in the epoxy resin. The epoxy resin composition containing the modified boron nitride has high peel strength and excellent bonding properties while achieving high thermal conductivity, thereby achieving excellent comprehensive effects of high thermal conductivity and high reliability in the metal foil-clad laminate.

[0089] (2) The present invention designs and optimizes the components and ratios of the epoxy resin composition so that the thermal conductivity of the copper-clad laminate containing the epoxy resin composition is ≥4.86 W / m·k and the peel strength is ≥0.71 N / mm, and the copper-clad laminate has excellent thermal conductivity and heat dissipation performance, interlayer bonding strength and reliability. DETAILED DESCRIPTION

[0090] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0091] The preparation method of the modified boron nitride is described below in conjunction with specific preparation examples, but the preparation method of the modified boron nitride is not limited to these preparation examples.

[0092] In the following preparation examples, boron nitride, sintering aids, and other metal oxides are all commercially available chemicals; among them, boron nitride has a lamellar structure and is purchased from 3M, CFP003.

[0093] Preparation Example 1-6

[0094] Modified boron nitride AF, the preparation method is as follows:

[0095] Boron nitride, a sintering aid and optionally other metal oxides are weighed in parts by mass according to the ratio shown in Table 1, and physically dry mixed for 1 hour to obtain a mixture; the mixture is added to a grinding tool, and sintered in a nitrogen atmosphere according to the temperature, pressure and time shown in Table 1 to obtain a sintered product; the sintered product is a block sample, which is placed in a ball mill for wet ball milling at a speed of 3000 rpm for 1-5 hours, and the particle size of the zirconium beads is 1-10 mm; after ball milling, it is dried to obtain modified boron nitride particles; the preparation of modified boron nitride with different particle sizes is achieved by controlling the ball milling time.

[0096] Table 1

[0097]

[0098] In Table 1, the dosage units of boron nitride (BN), sintering aids, and other metal oxides are "parts" (parts by mass), and "--" means that the component is not added. The average particle size of the modified boron nitride is tested by laser diffraction method, and the testing instrument is Malvern laser particle size analyzer, model MS3000.

[0099] Preparation Example 7

[0100] Modified boron nitride G, the preparation method is as follows:

[0101] 96 parts of boron nitride and 4 parts of magnesium oxide are weighed by mass, and physically dry mixed for 1 hour to obtain a mixture; the mixture is added to a grinding tool, sintered at 700°C and 8GPa in a nitrogen atmosphere for 6 hours to obtain a block-shaped first sintered product, which is wet-milled in a ball mill at a speed of 3000 rpm for 2 hours. The particle size of the zirconium beads is 1-10mm, and the ball milling is dried to obtain primary particles; the primary particles are placed in a high-temperature furnace, sintered at 1800°C in a nitrogen atmosphere for 6 hours, and then the sintered product is placed in a ball mill for wet-milling, and the ball milling is dried to obtain a modified boron nitride G with an average particle size of 15μm.

[0102] The epoxy resin composition and application of the present invention will be described in detail below by taking a number of embodiments as examples, but the epoxy resin composition and application of the present invention are not limited to these embodiments.

[0103] In the following examples, the materials for which the preparation methods are not provided are all commercially available chemicals, and the specific information is shown in the following table:

[0104] category source Epoxy resin A, ZX1059 Nippon Steel Corporation Brominated Epoxy Resin, BEB531A80P Changchun Chemical Co., Ltd. Phenoloxy resin, YP-50EK35 Nippon Steel Corporation Curing agent: phenolic resin, SH4064 Shandong Shengquan Co., Ltd. Accelerator: 2-methylimidazole (2-MI) BASF Modified Boron Nitride AG Preparation Example 1-7

[0105] Examples 1-7, Comparative Examples 1-3

[0106] An epoxy resin composition, the types and amounts of the components are shown in Table 2, and the units of the amounts of the components are all "parts" (parts by mass).

[0107] A prepreg and a copper-clad laminate comprising the epoxy resin composition, the preparation method of which is as follows:

[0108] (1) mixing the various components of the epoxy resin composition with a solvent (ethylene glycol methyl ether) according to the formula amount, and uniformly dispersing them at room temperature to prepare a glue solution with a solid content of 80%; impregnating a glass fiber cloth with the glue solution, placing the glass fiber cloth in an oven at 155° C. and baking it for 5 minutes to obtain a prepreg with a thickness of 5 mil;

[0109] (2) 6 prepregs are stacked, copper foils are stacked on both sides thereof, and the prepregs are laminated and cured in a hot press at 210° C. and 5 MPa pressure for 2 h to obtain the copper clad laminate.

[0110] The copper clad laminate is subjected to a performance test, and the specific method is as follows:

[0111] (1) Thermal conductivity: The thermal conductivity of the plate is tested according to the test method in standard ASTM-D5470;

[0112] (2) Peel strength: Refer to the test conditions in IPC-TM-650 2.4.8 method to test the peel strength of the sheet;

[0113] The performance test data is shown in Table 2.

[0114] Table 2

[0115]

[0116]

[0117] According to the performance test data in Table 2, the present invention compounds the modified boron nitride prepared by a specific method with an epoxy resin system, so that the epoxy resin composition and the copper clad laminate prepared therefrom have high thermal conductivity and high peel strength, wherein the thermal conductivity of Examples 1-5 is 4.86-14.7 W / m·k, and the peel strength is 0.71-1.35 N / mm, having excellent comprehensive performance.

[0118] In Example 6, the amount of modified boron nitride used is relatively small, resulting in a decrease in the thermal conductivity of the copper clad laminate; in Example 7, the amount of modified boron nitride used is too large, resulting in poor processability of the composition and failure to prepare a qualified product.

[0119] According to the comparison between Example 4 and Comparative Examples 1-3, it can be seen that the amount of sintering aid used in the preparation of the modified boron nitride E used in Comparative Example 1 is too small, resulting in an insignificant modification effect. The modified boron nitride E still cannot achieve a high filling ratio, has poor processability, and cannot produce a qualified product. Unmodified boron nitride filler is used in Comparative Example 3, which also cannot be highly filled and cannot produce a qualified product. The modified boron nitride F in Comparative Example 2 uses too much sintering aid, which affects the thermal conductivity of the material and causes the thermal conductivity of the plate to be significantly reduced.

[0120] The applicant declares that the present invention illustrates the epoxy resin composition and its application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An epoxy resin composition, characterized in that The epoxy resin composition comprises a combination of epoxy resin, a curing system and modified boron nitride; The modified boron nitride is prepared by the following method, which comprises: mixing boron nitride and a sintering aid, sintering and crushing to obtain the modified boron nitride; The sintering aid includes any one of calcium oxide, magnesium oxide, silicon oxide, yttrium oxide, niobium oxide, and potassium feldspar, or a combination of at least two thereof; based on the total mass of the boron nitride and the sintering aid being 100%, the mass of the sintering aid is 1-10%.

2. The epoxy resin composition according to claim 1, characterized in that The epoxy resin includes any one or a combination of at least two of bisphenol A epoxy resin, bisphenol F epoxy resin, phenolic epoxy resin, phosphorus-containing epoxy resin, isocyanate-modified epoxy resin, novolac epoxy resin, biphenyl epoxy resin, dicyclopentadiene epoxy resin, naphthalene-containing epoxy resin, alicyclic epoxy resin, and brominated epoxy resin; Preferably, the mass percentage of the epoxy resin in the epoxy resin composition is 8-70%, more preferably 9-50%.

3. The epoxy resin composition according to claim 1 or 2, characterized in that The curing system includes a curing agent and / or an accelerator; Preferably, the mass percentage of the curing system in the epoxy resin composition is 0.01-30%; Preferably, the curing agent includes any one or a combination of at least two of phenolic resin, cyanate resin, active ester, modified polyphenylene ether resin, maleimide resin, anhydride curing agent, amine curing agent, and benzoxazine resin; Preferably, the phenolic resin includes any one or a combination of at least two of bisphenol A phenolic resin, phosphorus-containing phenolic resin, phenol-type phenolic resin, biphenyl-type phenolic resin, dicyclopentadiene-type phenolic resin, and naphthalene-containing phenolic resin; Preferably, the accelerator comprises any one or a combination of at least two of imidazole compounds, organic complexes, tertiary amines, tertiary phosphines, and quaternary ammonium salts, and imidazole compounds are further preferred; Preferably, the imidazole compound includes any one of 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole, 1-benzyl-2-methylimidazole, 2-heptadecylimidazole, 2-isopropylimidazole, 2-phenyl-4-methylimidazole, 2-dodecylimidazole, and 1-cyanoethyl-2-methylimidazole, or a combination of at least two thereof; Preferably, the mass percentage of the accelerator in the epoxy resin composition is ≤8%.

4. The epoxy resin composition according to any one of claims 1 to 3, characterized in that The average particle size of the modified boron nitride is 0.1-30 μm; Preferably, the mass percentage of modified boron nitride in the epoxy resin composition is 30-92%, and more preferably 50-90%.

5. The epoxy resin composition according to any one of claims 1 to 4, characterized in that The mixed raw materials also include other metal oxides; Preferably, the other metal oxides include aluminum oxide and / or beryllium oxide; Preferably, based on the total mass of the boron nitride, the sintering aid and the other metal oxides being 100%, the mass of the other metal oxides is 1-10%; Preferably, the sintering is carried out in an inert atmosphere; Preferably, the inert atmosphere includes a nitrogen atmosphere and / or an argon atmosphere.

6. The epoxy resin composition according to any one of claims 1 to 5, characterized in that The sintering method includes a one-stage sintering method or a two-stage sintering method; Preferably, the sintering temperature of the one-stage sintering method is 700-2000°C; Preferably, the sintering pressure of the one-stage sintering method is 1-10 GPa; Preferably, the sintering time of the one-stage sintering method is 2-8 hours; Preferably, the two-stage sintering method comprises: mixing boron nitride, a sintering aid and optionally other metal oxides, performing a first sintering and a first crushing to obtain primary particles; performing a second sintering and a second crushing on the primary particles to obtain the modified boron nitride; Preferably, the temperature of the first sintering is 300-700°C; Preferably, the first sintering pressure is 1-10 GPa; Preferably, the first sintering time is 1-8h; Preferably, the temperature of the second sintering is 700-2000°C; Preferably, the second sintering time is 2-8 hours.

7. A prepreg, characterized in that: The prepreg comprises a reinforcing material and an epoxy resin composition according to any one of claims 1 to 6 attached to the reinforcing material; Preferably, the epoxy resin composition is attached to the reinforcing material by impregnation and drying.

8. A thermally conductive resin film, characterized in that: The material of the thermally conductive resin film comprises the epoxy resin composition according to any one of claims 1 to 6; Preferably, the thermally conductive resin film is obtained by coating the epoxy resin composition on a release material and then drying and / or semi-curing the epoxy resin composition.

9. A metal foil-clad laminate, characterized in that: The metal foil-clad laminate includes a metal foil and at least one of the prepreg according to claim 7 and the thermally conductive resin film according to claim 8 .

10. A printed circuit board, characterized in that: The printed circuit board comprises at least one of the prepreg according to claim 7, the thermally conductive resin film according to claim 8, and the metal foil-clad laminate according to claim 9.

Citation Information

Patent Citations

  • High-thermal-conductivity film for aluminum-based copper-coated plate, and preparation method thereof

    CN102993996A

  • Epoxy resin composition, metal-based copper-clad plate and manufacturing method thereof

    CN103694644A

  • Preparation method of high-thermal-conductivity and high-heat-resistance CEM-3 copper-clad plate for LED

    CN116080213A

  • Boron nitride aggregate, thermosetting resin composition containing boron nitride aggregate, and applications thereof

    CN109988409A

  • Composite heat-conducting filler, resin composition, prepreg, circuit substrate and printed circuit board

    CN117510994A